Constraints and opportunities to rabbit production in Zimbabwe: A case study of the Midlands Province, Zimbabwe - Gono, Robert K; Dube, John; Sichewo, Petronillah R; Muzvondiwa, John V (World Wide Journals, 2022)
A study was conducted to determine the productivity and constraints of smallholder rabbit production in the Mberengwa and Zvishavane districts of the Midlands Province in Zimbabwe. 42 households were randomly selected to respond to a standard questionnaire. 79% of the respondents had an average rabbit rearing experience of less than five years. The average clutch size per household was less than 10 mature rabbits. The rabbits were acquired through purchase (88%), gifts (7%), or in exchange for labor. However 76% of the rabbits were sourced from within the local area. Only 17% of the farmers fed commercial feeds. The prevalent diseases were mange (68%), coccidiosis (24%), and foot rot (8%). 23% of the farmers used veterinary drugs and medicines to treat the common diseases, whilst 67% sourced the locally available herbs and plants for the same purpose. Survivability of the rabbits was significantly affected (P< 0.001) and strongly correlated (r= 0.) with housing system. Rabbit meat was mainly used to generate household income and for home consumption.